2022
DOI: 10.3390/ijerph19031724
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatology of Fibromyalgia Syndrome in Men: A Mixed-Method Pilot Study

Abstract: Fibromyalgia syndrome (FMS) is characterized by generalized chronic musculoskeletal pain, fatigue, and sleep disturbance, as well as cognitive, somatic, and other symptoms. Most people affected by FMS are women, and studies analyzing this condition in men are scarce. In this study, we discuss the physical and psychological symptoms of FMS in men, analyze the possible side effects of pharmacological therapies, and explore the impact of the illness comparing these results between the different classification gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…The Spanish health and social system provide healthcare coverage and pension provision (27). Participants in our study also identified negative emotions like anger, frustration, and impotence experiences with the misunderstandings by some healthcare professionals with did not contribute to their improvement (11,22,23). The misunderstanding of the disease and lack of empathy on the part of family, friends, and health professionals caused emotions of anger, rage, frustration, and helplessness (11,25).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The Spanish health and social system provide healthcare coverage and pension provision (27). Participants in our study also identified negative emotions like anger, frustration, and impotence experiences with the misunderstandings by some healthcare professionals with did not contribute to their improvement (11,22,23). The misunderstanding of the disease and lack of empathy on the part of family, friends, and health professionals caused emotions of anger, rage, frustration, and helplessness (11,25).…”
Section: Discussionmentioning
confidence: 63%
“…Participants in our study also identified negative emotions like anger, frustration, and impotence experiences with the misunderstandings by some healthcare professionals with did not contribute to their improvement (11,22,23). The misunderstanding of the disease and lack of empathy on the part of family, friends, and health professionals caused emotions of anger, rage, frustration, and helplessness (11,25). Also, men reported the lack of recognition of FMS in men has such a strong influence on men who are affected because it is not believed that men can suffer from it, as it is mostly associated with the female sex (35).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…On the other hand, this sex bias may also affect men by being underdiagnosed which delays assessing the peculiarities of FMS in this population and its best treatment approach [ 13 , 66 ]. Studies on men’s illness experience with FMS have found some differences with women’s symptomatology [ 66 , 67 , 68 ]. For instance, Miró and colleagues [ 66 ] found that emotional distress and sleep disorders affect cognitive functions differently between sex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in urban areas, prevalence reaches 0.7 and 11.4%, and in rural areas between 0.1 and 5.2% [ 3 ]. Studies also point to the presence of fibromyalgia in men [ 4 6 ]. Although the prevalence of fibromyalgia does not have the same notoriety as other rheumatologic conditions, its annual economic impact is considered very high [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%